Implementasi Fuzzy Simple Additive Weighting (SAW) sebagai Pendukung Keputusan pada Beasiswa Penelitian - Rahman Abdillah (Universitas Indraprasta PGRI Jakarta, 2017)
The aim of this research is designing decision support systems (DSS) which helps the decision maker to acquire the decision applied to the candidates which register to the research scholarship program (Riset Inovatif Produktif/RISPRO) from Lembaga Pengelola Dana Pendidikan (LPDP), held by the Ministry of Finance RI. This research use Fuzzy Simple Additive Weighted (FSAW) as a methodology by classified attributes from each criteria rate, then calculate weights of each criteria and rank them as a final result. Decision maker will get recommendation of potential awardees base on rank and score from each candidates. The presented of decision support systems that has been designed hope can help the decision maker to do the process of determining scholarships recipient faster and accurately.